THE ROLE OF THE CREATIVE ECONOMY IN THE SOCIO-ECONOMIC DEVELOPMENT OF REGIONS (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The article analyzes the role of the creative economy in the socio-economic development of regions, including the importance of developing creative entrepreneurship in the field of culture and art. It considers the establishment of infrastructure for creative industry parks based on public-private partnerships. Advanced foreign experiences in the development of the creative industry have been studied. Proposals and recommendations aimed at developing the creative industry in Uzbekistan have been developed.
Keywords: accelerators, public-private partnership, creative economy and industry, creative clusters, creative entrepreneurs, creative projects, creative workshops, coworking center, culture and art, intellectual activity, startup.